Recent advances of exosomes in age-related macular degeneration - Gu, Feng; Jiang, Jiyu; Sun, Peng (Frontiers in Pharmacology, 2023)
Exosomes are 30-150 nm extracellular vesicles that are secreted by almost all types of cells. Exosomes contain a variety of biologically active substances, such as proteins, nucleic acids, and lipids, and are important in the intercellular communication of biological mediators involved in nerve injury and repair, vascular regeneration, immune response, fibrosis formation, and many other pathophysiological processes. Although it has been extensively studied in the field of cancer, the exploration of ocular diseases has only just begun. Here, we discuss the latest developments in exosomes for age-related macular degeneration (AMD), including the pathogenesis of exosomes in AMD, their potential as diagnostic markers, and therapeutic vectors of the disease. Finally, the study of exosomes in AMD is still relatively few, and more detailed basic research and clinical trials are needed to verify its application in treatment and diagnosis, so as to adopt more personalized diagnosis and treatment strategies to stop the progression of AMD.